Plasma proteomic signatures of liver steatosis and fibrosis in people living with HIV: a cross-sectional studyResearch in context - Louise E. van Eekeren; Quirijn de Mast; Elise M.G. Meeder; Adriana Navas; Albert L. Groenendijk; Marc J.T. Blaauw; Wilhelm A.J.W. Vos; Nadira Vadaq; Jéssica C. Dos Santos; Joost Rutten; Niels P. Riksen; Jan van Lunzen; et al. (EBioMedicine)
Summary: Background: Insights into the mechanisms driving metabolic dysfunction-associated steatotic liver disease (MASLD) in people living with HIV (PLHIV) remain limited. Plasma proteomics holds promise for biomarker discovery and the elucidation of biological mechanisms. Methods: We performed cross-sectional analyses on data from 1036 virally suppressed PLHIV using antiretroviral treatment (ART) from the Dutch multi-centre 2000HIV cohort. Participants underwent transient elastography to assess liver steatosis (controlled attenuation parameter (CAP) ≥263 dB/m) and -fibrosis (liver stiffness measurement (LSM) ≥7.0 kPa). Plasma protein concentrations (n = 2367) (Olink® Explore Panel) were compared between PLHIV with vs. without liver steatosis and PLHIV with vs. without fibrosis. Enriched pathways (using GO, KEGG and Reactome libraries) and correlations with clinical characteristics were assessed, and analyses were stratified by BMI category. In addition, concentrations of 242 proteins were compared between individuals (“controls”) with and without liver steatosis (ratio of methylene:methylene and water >5.6% on magnetic resonance spectroscopy) from a separate cohort (300-OB), all having a BMI >26 kg/m2. Findings: Steatosis and fibrosis were associated with 67/2367 (2.2%) and 17/2367 (0.7%) differentially expressed proteins (DEP), respectively, enriched in mostly metabolic pathways. Immunoglobulin superfamily member 9 (IGSF9) was amongst the top DEP associated with both steatosis and fibrosis. Stratifying by BMI revealed 8/2367 DEP associated with steatosis in lean- and 12/2367 DEP in overweight/obese individuals, with two shared DEP (IGSF9 and GHR). Conversely, protein signatures of overweight/obese PLHIV (32/242 DEP) and overweight/obese HIV-uninfected individuals (32/242 DEP) exhibited substantial overlap with 16 shared DEP. Notably, DEP correlated with HIV characteristics in lean individuals but not in overweight/obese PLHIV. Interpretation: Lean and overweight/obese PLHIV exhibit distinct proteomic signatures associated with liver steatosis, with the former being more strongly correlated with HIV-specific factors and ART. In addition, we identified a protein, IGSF9, strongly related to liver fibrosis and steatosis across BMI categories. Funding: The 2000HIV study is funded by ViiV Healthcare.